Linking Corporate Social Responsibility to Workplace Deviant Behaviors: Mediating Role of Job Satisfaction - Memon, Khalid Rasheed; Zada, Muhammad; Ghani, Bilqees; Ullah, Rezwan; Azim, Mohammad Tahlil; Mubarik, Muhammad Shujaat; Vega-Muñoz, Alejandro; Castillo, Dante (Frontiers in Psychology, 2021)
The purpose of this article is to present a mechanism through which the deviant work behaviors of employees can be dealt-with positively through corporate good deeds in the form of fulfilling social responsibilities. Based on the spirit of social identity theory and social exchange theory, the study explores the relationships of various deviant behaviors with CSR through the mediation mechanism of job satisfaction. Data were collected from 385 employees of 40 large manufacturing organizations involved in CSR activities operating in Pakistan. A self-report survey was conducted using a close-ended questionnaire. Data analysis was performed using SEM through Mplus 7. The results reveal that both internal and external CSR contribute to the reduced level of turnover intention, counterproductive work behaviors, and prohibitive voice behaviors. Job satisfaction fully mediates the relationship for internal CSR while partially mediates for external CSR. The study persuades the practitioners to avail approaches that convey the feelings of care, concern, and safety, representing internal CSR practices through diverse HR interventions, organizational support, and justice. They should also keep up the socially responsible behaviors aiming towards the larger community.